Excitation of surface field cavity and coherence of electromagnetic field scattering on two-dimensional cylindrical lattice - Konoplev, I; Fisher, L; Cross, A; Phelps, A; Ronald, K; Thumm, M (2010)
The excitation of a surface field cavity based on a large area two-dimensional cylindrical lattice and surface field scattering within the cavity are investigated. It is shown that the interaction between surface and volume fields via distributed scatterers becomes coherent and the cavity excitation takes place only when it is irradiated with a near cut-off transverse-magnetic polarized field. The coherence of the radiation observed from the surface field scattering is investigated. © 2010 American Institute of Physics.